Sustainable Marketing Communications as Competitional Advantage for Digital Products at the Example of E-Books - Bednarek, Felix Samuel; Stříteský, Václav; Hommerová, Dita; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The economy and society are shaped by digitalization and sustainability. Companies recognize the benefits of digital business models through increased services and automation. Consumers, especially Generation Z, are accustomed to digital products' convenience and advantages. Alongside the digital revolution, there is a shift towards sustainability, focusing on environmental and social responsibility. Companies play a key role in promoting a greener and fair world and see sustainability as a new strategic opportunity. This dual trend is evident in the e-book market. E-books offer advantages like easier access and are a more sustainable alternative to printed books. However, current literature lacks insights into the competitive advantage of e-books' sustainable characteristics. This research aims to evaluate sustainability as a competitive advantage for digital products, using the German e-book market as an example. Therefore, this research paper answers the question “How can sustainable marketing communications targeted at Generation Z consumers be used to establish a competitive advantage of digital products at the example of e-books on the German e-book market?” The study involves three steps: reviewing 60 German e-book and book publishers about the implementation of sustainable marketing communications, conducting three focus groups with Generation Z consumers, and a field experiment to measure the success of sustainable marketing communications. This research paves the way for future studies on the competitive efficiency of sustainability for digital products and offers practical implications for companies.
Vedoucí práce: Václav Stříteský
Závěrečná práce - Institut celoživotního vzdělávání (DBA)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet